MEDIA VIDEO INTERAKTIF UNTUK MENINGKATKAN MOTIVASI BELAJAR PAI ANAK: A SYSTEMATIC LITERATURE REVIEW - Fatiha Amila Sholihah; Usvatun Khasanah; Imam Makruf (Al-ATHFAL: Jurnal Pendidikan Anak, 2026)
This study aims to analyze the implementation of video-based interactive learning media in Islamic Religious Education (IRE) and its potential for enhancing student learning motivation. The method used was a Systematic Literature Review (SLR) employing the PRISMA approach, which involved the stages of identification, screening, eligibility assessment, and inclusion of relevant literature. The results of the study regarding implementation indicate that the use of platforms such as EdPuzzle and H5P enables the presentation of PAI material in a more engaging, contextual, and participatory manner, although their effectiveness remains limited by infrastructure constraints and teachers’ digital literacy. Regarding the potential for increased motivation, it was found that interactive video media significantly enhances students’ attention, enthusiasm, and engagement in PAI learning.